Leading without authority : how the new power of co-elevation can break down silos, transform teams, and reinvent collaboration - Ferrazzi, Keith (New York : Currency, 2020)
"The author of the #1 New York Times bestseller Never Eat Alone redefines collaboration for the twenty-first century with a radical new workplace operating system in which leadership no longer demands an official title. Many are quick to respond to the mounting pressures facing today's organizations by blaming the pace of technological change. But bestselling author, CEO, and coach to Fortune 100 companies Keith Ferrazzi disagrees. This era of explosive change, he says, has merely exposed the flaws in how we have always worked. At a time when constant innovation, agility, and speed of decision-making can mean the difference between success and failure, he says, we can no longer afford to waste time navigating the complex chains of command or bureaucratic bottlenecks present in most companies. In times like these, the ability to lead without authority is an essential workplace competency. Enter a bold new methodology Ferrazzi calls co-elevation. With the guiding ethos of "going higher together," co-elevation allows us to turn colleagues and partners into teammates. And you don't have to have formal authority, or direct reports, to do it. In fact, the other person doesn't even need to be aware of your efforts. You simply have to marshal a commitment to a shared mission and care about the success and development of others as much as you care about your own. By helping others to be better at what they do, we create a level of trust, candor, mutual accountability, and purpose that exceeds what could have been accomplished under the status quo. In Leading Without Authority, Ferrazzi draws on over a decade of research and over thirty years helping CEOs and senior leaders drive innovation and build high-performing teams to reveal how we can all transform our business and our relationships with the people around us. The result is a new roadmap for thriving amid the disruptive pressures afflicting every industry"--
Includes bibliographical references and index.
Keywords: Leadership; Organizational behavior; Management -- Employee participation